COVID-19 countermeasures, sporting events, and the financial impacts to the North American leagues - Ehrlich, J. A.; Ghimire, S.; Khraiche, M.; Raza, M. F. (Managerial Finance, 2020)
Purpose: The purpose of this paper is to analyze how the coronavirus disease 2019 (COVID-19) countermeasures will affect the financing of the North American leagues. In particular, we focus on the missed revenue from gate receipts for the Big Four leagues. Design/methodology/approach: The authors forecast the 2020 revenue for each of the four major leagues under two scenarios: (1) expected revenue under the normal conditions of fans in attendance and (2) expected revenues in the absence of fans due to the countermeasures in place. Then, the authors calculate the loss in gate receipts as a difference in the revenue under fans and no-fans scenarios. Findings: Based on the current estimates, the combined financial loss of the clubs from NFL, MLB, NBA and NHL is expected to be above 6.8bn dollars in gate receipts alone. Practical implications: The findings are useful to the league management to prepare for the suboptimal financial situation. Originality/value: To the best of our knowledge, this is the first study that explores the effect of the COVID-19 pandemic across the major league sports leagues in North America.